A Functional Variant in the Aquaporin-3 Promoter Modulates Its Expression and Correlates With Resistance to Porcine Epidemic Virus Infection in Porcine Intestinal Epithelial Cells - Wang, Haifei; Bi, Zhenbin; Dai, Kaiyu; Li, Pinghua; Huang, Ruihua; Wu, Shenglong; Bao, Wenbin (Frontiers in Microbiology, 2022)
Porcine epidemic diarrhea virus (PEDV) causes a highly contagious intestinal disease in neonatal pigs. Aquaporin-3 (AQP3) plays important roles in maintenance of intestinal barrier function and regulation of immune responses. However, the roles of AQP3 in mediating PEDV infection to host cells and the regulatory mechanisms of AQP3 expression remain poorly understood. Here, we identified a 16 bp (GGGCGGGGTTGCGGGC) of insertion mutation in AQP3 promoter in Yorkshire pigs, with the frequencies of 49.3% of heterozygotes and 31.3% of mutant homozygotes. Functional analysis by luciferase activity assay indicated that the insertion mutation results in significant enhancement in AQP3 transcriptional activity (P < 0.01). Mechanistic analysis showed that the inserted sequence creates binding sites for transcription factor CEBPA, which promotes the expression of AQP3. Downregulation of AQP3 by shRNA silencing in porcine intestinal epithelial cells revealed obvious increases in PEDV copies. Expression of proinflammatory cytokines (IL-6, IL-8, and IL-18) and interferons (IFN-α and IFN-β) were significantly reduced (P < 0.01) in AQP3 knockdown cells upon PEDV infection. Furthermore, decreased level of ZO-1 protein was also detected in AQP3 knockdown cells in response to PEDV infection. Our findings suggested a previously unknown mechanism linking effects of promoter genetic variants on AQP3 expression, revealed the roles of AQP3 in response to PEDV pathogenesis, and highlighted the potential of the 16 bp of insertion mutation as candidate genetic markers for selective breeding of pigs against porcine epidemic diarrhea.